Emily windsnap and the monster from the deep ebook - Kessler, Liz (Emily Windsnap, 2010)
"High-action adventure, a plucky protagonist, and whimsical illustrations enliven this sea fantasy, which will be most thoroughly appreciated by series followers." — Booklist Picture an island set in a glittering blue sea, sparkling with white sand and palm trees, a secret place where humans and merfolk live together. To Emily Windsnap — half mermaid, half human — her new home is perfect. That is, until Emily ruins everything by waking a legendary sea monster known as the kraken from its hundred-year sleep. . . . An enchanting tale with a fabulous monster, engaging characters, and plenty of mermaid magic, this second fantasy about Emily Windsnap is filled with charm and warmth.